Aspirin and poetry: Did João Cabral de Melo Neto suffer from acetylsalicylic acid-overuse headache? - Cardoso, Milena; Meneses Neto, Pedro; Silva-Néto, Raimundo Pereira (Headache Medicine, 2023)
Introduction João Cabral de Melo Neto is considered one of the most important Brazilian poets of all time. He suffered from severe headaches for the longest part of his life, being diagnosed with migraine. He took a significant amount of acetylsalicylic acid pills every day for many years. Objective The objective of this narrative review includes identifying how headache and its treatment influenced João Cabral de Melo Neto's poetry as well as analyzing the correlation between Melo Neto's migraine diagnosis and his documented overuse of aspirin and investigating the possibility of an acetylsalicylic acid-overuse headache diagnosis. Methods The authors thoroughly read biographical books and interviews about the life of João Cabral de Melo Neto. They systematically documented all references to headaches and aspirin. Melo Neto's clinical case documented in his biography and interviews were juxtaposed with The International Classification of Headache Disorders (ICHD-3) diagnostic criteria for acetylsalicylic acid-overuse headache diagnosis. Results The word “aspirin” appears 8 times in 6 of Melo Neto’s poems. He compares it to the sun, attributing to it the capacity to refocus a "blurred body" (his state during a headache). The poet reported that took one aspirin pill every hour every day, for several years. Conclusions Headache and the use of acetylsalicylic acid influenced João Cabral de Melo Neto’s poetry and life. He presented a risk behavior for developing medication overuse headache, specifically its subform: acetylsalicylic acid-overuse headache.